Politik Etnisitas Dalam Upaya Pemekaran Provinsi Kotawaringin - Ricky Zulfauzan; Kris Nugroho; Dwi Windyatuti (Institut Teknologi Sepuluh Nopember, 2019)
This study aims to provide a descriptive analysis of ethnicity politics from theperspective of Glazer and Moynihan